Reinforcing Motivation and Engagement by Behavioral Design in Learning Systems - Ademi, Neslihan; Loshkovska, Suzana; CHorbev, Ivan (My University, 2019)
In this paper, the opportunity of implementing behavioral design into learning systems is elaborated from a theoretical aspect. Technology has power to change human behavior and habits. Anywhere anytime connection concept provides ease of access, variable content, low cost, which attracts the users affecting many aspects of life. Education is affected from this trend and it led instructors to move e-learning environments. Although e-learning systems have many advantages, motivating students online can be challenging because of content, isolation, poor communication with instructors, and lack of connection between content and the students’ needs. On the other hand, most of the students are already addicted to digital content due to habit forming products in daily life. Once they become addicted to technology, the books and traditional education or content are not interesting for them. The biggest problem of the education can be considered as the students who are not interested with the content and do not want to learn. With the behavioral design aware educational technologies, permanence, continuity and qualification can be given to learning, engagement level can be improved and better study habits can be formed.
Keywords: E-learning, Motivation, Engagement, Study Habits, Behavioral Design, Habit Forming